2018
DOI: 10.1021/acssuschemeng.8b05217
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of B and O Dopants for Aerobic Oxidative Coupling of Amines to Imines

Abstract: Boron-doped mesoporous carbon material (B–C) was fabricated by annealing boric acid and sustainable cellulose at high temperature in inert atmosphere. This heteroatom-doped carbon exhibited excellent catalytic activity and high selectivity in the oxidative coupling of amine to imines. Owing to the recyclable utilization of boric acid involved in the preparation of B–C and a kind of earth abundant natural biomass being the carbon source, this metal-free carbon catalyst could be regarded as a kind of green and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…To further clarify the reasons that why Pd–chitin-150 is more active and stable during the reaction, we use XPS to analyze the atomic environment on the surface of the catalyst. For the XPS C 1s spectra of Pd–chitin- T shown in Figure a, three deconvolved peaks located at 284.5, 286.5, and 288.2 eV can be attributed to carbon atoms in the form of C–C, C–O/C–N, and N–CO, which are similar to the XPS C 1s spectrum of pure chitin. The XPS N 1s spectra of Pd–chitin- T can be deconvolved into two peaks of N-(C) 3 and C–N–H located at 399.7 and 400.8 eV respectively .…”
Section: Resultsmentioning
confidence: 62%
“…To further clarify the reasons that why Pd–chitin-150 is more active and stable during the reaction, we use XPS to analyze the atomic environment on the surface of the catalyst. For the XPS C 1s spectra of Pd–chitin- T shown in Figure a, three deconvolved peaks located at 284.5, 286.5, and 288.2 eV can be attributed to carbon atoms in the form of C–C, C–O/C–N, and N–CO, which are similar to the XPS C 1s spectrum of pure chitin. The XPS N 1s spectra of Pd–chitin- T can be deconvolved into two peaks of N-(C) 3 and C–N–H located at 399.7 and 400.8 eV respectively .…”
Section: Resultsmentioning
confidence: 62%
“…Among them, those routes based on heterogeneous photocatalysis have been considered as efficient and environmentally benign for the synthesis of imines. They represent a technology that can reduce environmental hazards and decrease energy consumption with high atom efficiency. Thereby, we used the oxidative coupling of amines to imines under visible-light irradiation to evaluate the photocatalytic performance of the ZnS–C 3 N 4 composites. As shown in Table and Figure S7, the oxidative coupling of benzylamine (0.5 mmol) as a model substrate was carried out in the presence of molecular oxygen (as oxidant) under visible-light irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…In another study in 2018, Liu and co-workers 245 reported that boron-doped mesoporous carbon (B-C) can be used as a high-performance heterogeneous catalyst for the oxidative coupling of amines and the relevant imines were furnished in good to high yields and selectivity ( Scheme 33 ). This heteroatom-doped carbon was synthesized by mixing earth-abundant biomass cellulose and H 3 BO 3 , followed by annealing in an inert atmosphere at elevated temperature ( Fig.…”
Section: Recent Progress On Heteroatom-doped Carbon Materials As Hete...mentioning
confidence: 99%